The quick-reference guide to sexuality & relationship counseling - Clinton, Timothy E., 1960-; Laaser, Mark R. (Grand Rapids, Mich. : Baker Books, 2010)
One of the foremost counseling needs in our day is help with sexuality and relationship issues. But sometimes those who are faced with helping the hurting could use a little more information about the problems that people bring to them. The Quick-Reference Guide to Sexuality and Relationship Counseling provides the answers. --from publisher description.
Part I: Sex and relationships -- Sexual intimacy and delight -- Sexual desire and expectations -- Threats to sexual intimacy -- Increasing sexual satisfaction -- Stress and sex -- Birth control and reproduction -- Infertility -- Part II: Sexual problems and relationship challenges -- Low sexual desire -- Orgasmic disorders -- Premature ejaculation -- Sexual arousal disorder -- Sexual pain disorder -- Masturbation and self-sex -- Oral sex -- Anal sex -- Sexually transmitted diseases -- HIV transmission and AIDS -- Adult survivors of sexual abuse -- Infidelity and affairs -- Forgiveness and rebuilding trust -- Part III: Sexual addiction and deviance -- Sex and romance addiction -- Pornography -- Polyamory and group sex -- Exhibitionism and voyeurism -- Fetishism -- Frotteurism -- Sadism and masochism -- Sexual violence and rape -- Prostitution and sexual exploitation -- Pedophilia -- Sexual harassment -- Part IV: Gender identity issues -- Homosexuality -- Gender identity disorder -- Transvestic fetishism -- Part V: Sexual issues in parenting and family life -- Raising sexually healthy children -- Sexually active kids and teens -- Teenage pregnancy and parenting -- Incest -- Singles and sexuality -- Elder sex.
Includes bibliographical references (pages 285-288).
Keywords: Sex -- Religious aspects -- Christianity -- Handbooks, manuals, etc; Pastoral counseling -- Handbooks, manuals, etc; Counseling -- Handbooks, manuals, etc